2021
DOI: 10.4491/eer.2021.197
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 lockdown improves air quality in Morocco

Abstract: Several measures have been taken to mitigate the effects of the COVID-19 pandemic. In this context, almost all non-essential activities in Morocco have been halted since March 20, 2020. From that date, Morocco announced the lockdown for one month and it was extended until June 10, 2020. The main objective of this paper is to study the effects of the lockdown measures on air quality, by analyzing dust PM 2.5 , NO 2 , and O 3 . The dust PM 2.5 analysis was carried out from 2016 to 2020. NO 2 and O 3 analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Masaki et al ( 2020 ) reported a decrease in the level of NO 2 in urban centres in SSA by 11% in April 2020 compared to monthly quantities in 2018 and 2019. Over Morocco, Sekmoudi et al ( 2022 ) investigated changes in surface dust PM 2.5 from 2016 to 2020 and O 3 and NO 2 from 2019 and 2020. The findings showed a decrease in PM 2.5 and NO 2 by about 10 and 4%, respectively, while O 3 increased by about 1%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masaki et al ( 2020 ) reported a decrease in the level of NO 2 in urban centres in SSA by 11% in April 2020 compared to monthly quantities in 2018 and 2019. Over Morocco, Sekmoudi et al ( 2022 ) investigated changes in surface dust PM 2.5 from 2016 to 2020 and O 3 and NO 2 from 2019 and 2020. The findings showed a decrease in PM 2.5 and NO 2 by about 10 and 4%, respectively, while O 3 increased by about 1%.…”
Section: Resultsmentioning
confidence: 99%
“…Dasgupta & Robinson, 2021 ; Oxfam, 2022 ; Shifa et al, 2021 ) observed that closure of businesses will likely widen the existing economic and gender inequality in SSA if not well addressed. During the pandemic, when most countries enforced lockdown, many cities across Africa and beyond recorded a reduction in the level of GHG emissions and an improvement in air quality (McFarlane et al, 2021 ; Sekmoudi et al, 2022 ; Shikwambana & Kganyago, 2021 ). On top of lockdowns helping to improve the air quality, the compliance of the public to limit movements and meaningful socio-economic activities illustrates how forcing people to sacrifice in the near-term for long-term gain can lower the risk of existential calamities such as climate change (Yohe, 2020 ).…”
Section: Discussionmentioning
confidence: 99%